(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article explores effective strategies for preventing deviant behavior in adolescents. It provides an overview of key concepts, discusses various prevention methods, presents research findings, and offers insights for future interventions. The article emphasizes the importance of positive parenting, education, peer influence, mentoring, mental health support, community involvement, and early intervention in promoting healthy adolescent development.